Uptake and reactivity of sulfur dioxide gas onto Icelandic volcanic dusts - Urupina, Darya (HAL CCSD, 2020)
This thesis investigates the interactions of sulfur dioxide (SO2) gas with Icelandic Volcanic Dusts. Five natural volcanic dust samples were used for the study: Hagavatn, Mýrdalssandur, Maelifellssandur, Dyngjusandur and Eyjafjallajökull. The heterogeneous interactions of gas-phase SO2 with volcanic dusts are investigated using a number of complimentary techniques. Temporal profiles of SO2 uptake and, more precisely, the steady state uptake coefficients have been determined experimentally. These are important kinetic parameters that can be implemented in models. Mechanisms of formation of various surface species resulting from the interactions of SO2 with the surface of dusts are proposed. A new method for quantification of surface sulphur species has been developed and validated. This method can now be used both for further laboratory investigations and in field measurements.It is evidenced that the interactions of SO2 gas with the volcanic dust is a long continuous process. The products formed on the surface are stable and definitely influence the mineral particle properties. It is evidenced that the interactions of SO2 gas and volcanic particles are highly influenced by humidity and by UV light. The influence of surface composition also plays an important role especially at levels of humidity equal or lower than 30% RH. This work emphasizes the importance of using relevant natural dust samples in order to study the heterogeneous atmospheric phenomena involving natural solid particles. Ces travaux de thèse portent sur l’étude des interactions du dioxyde de soufre (SO2) gazeux avec des poussières volcaniques islandaises. Ils intègrent cinq échantillons naturels de poussières volcaniques: Hagavatn, Mýrdalssandur, Maelifellssandur, Dyngjusandur and Eyjafjallajökull. Les interactions hétérogènes entre SO2 et les poussières volcaniques sont abordées avec plusieurs techniques expérimentales complémentaires. Les profils temporels associés à la capture de SO2, caractérisés par les coefficients de capture en régime ...